Altitude, heart rate variability and aerobic capacities - Schmitt, L.; Fouillot, J.-P.; Millet, G. P.; Robach, P.; Nicolet, G.; Brugniaux, J.; Richalet, J. P. (International Journal of Sports Medicine, 2008)
We analyzed the relationship between aerobic capacities and changes in heart rate variability (HRV) in Nordic-skiers during living high-training low (Hi-Lo). Eleven skiers trained for 18 days at 1200 m, sleeping at 1200 m (LL, n = 5) or in hypoxic rooms (HL, n = 6, 3 × 6 days at altitudes of 2500 - 3000 - 3500 m, 11 h · day-1). Measurements were performed before, during and two weeks after Hi-Lo. V·O2max, peak power output were not improved in HL nor in LL, whereas V·O2 and power at the respiratory compensation point (V·O2RCP and PRCP) increased by 7.5 % and 5.0 % only in HL. Significant changes in HRV occurred only in LL, in the standing position, including a 30 % (p < 0.05) increase in resting heart rate (HR), a 50 % (p < 0.05) decrease in total spectral power (TP) and a 77 % (p < 0.05) decrease in high frequency activity (HF). When all the subjects were pooled, the changes in HRV in the supine position were correlated to the changes in aerobic capacities, i.e., HF, LF and TP were correlated to V·O2RCP and HR, HF and TP were correlated to PRCP. This study confirms the relationship between HRV and changes in aerobic capacity, therefore highlighting the potential value of HRV for monitoring altitude training adaptations.